A Narrative Literature Review on Food Consumption Demand in Indonesia - Winda Noviyanti; Rosihan Adhani; Neka Erlyani; Musafaah Musafaah; Ardik Lahdimawan (Universitas Malahayati Lampung, 2026)
ABSTRACT Household food consumption in Indonesia continues to be dominated by carbohydrate-based staples, while the intake of protein-rich foods remains relatively low despite their importance for achieving adequate nutritional quality. Differences in food prices, household expenditure, and demographic characteristics contribute to varying levels of access to nutritious foods across Indonesian provinces, shaping diverse demand behaviors for carbohydrate- and protein-rich commodities. Although numerous studies in Indonesia have applied demand system approaches such as AIDS to analyze food consumption, existing evidence remains varied in focus and scope, underscoring the need to understand how nutritional demand has been examined across different contexts. This study aims to identify factors that influence food demand systems in Indonesia, with a specific focus on commodities that serve as primary sources of carbohydrates and protein. It seeks to map how previous research has conceptualized and analyzed key determinants of nutritional demand to provide a clearer foundation for further empirical investigation. A narrative literature review with a structured search strategy was conducted to gather Indonesian studies examining household food consumption demand. Searches were carried out across major academic sources using predefined keywords related to food demand, consumption behavior, and economic determinants. Relevant articles were screened based on their analytical focus and methodological approaches, and the final selection was examined comparatively to identify recurring frameworks and determinants influencing nutrient-based food demand. The review found that food demand for carbohydrate- and protein-rich commodities in Indonesia is consistently shaped by prices, household expenditure, and demographic characteristics. The examined studies also indicated variations in responsiveness to economic factors across commodity groups, highlighting notable differences in the sensitivity of carbohydrate staples compared to protein sources. These patterns reveal a set of determinants repeatedly emphasized in the literature, signaling their relevance for guiding subsequent empirical modeling of nutritional food demand. Keywords: Food Consumption Demand, Nutritional Demand System, Carbohydrate and Protein Commodities, Household Economic Determinants.